Heavy Dusty Over Head Stirrer Design and Construction - M.Ali Imron Rosyidi; Imam Tri Harsoyo; Patrisius Kusi Olla (Journal of Engineering, Electrical and Informatics, 2025)
This study aims to evaluate the performance of a designed overhead stirrer, specifically focusing on the accuracy of rotational speed (RPM) and time control (timer). Speed testing was conducted using a Fluke 931 tachometer as a reference instrument, while a digital stopwatch was used for time measurement. Speed tests were carried out at four levels: 500 RPM, 1000 RPM, 1500 RPM, and 2000 RPM, with three repetitions for each. The results showed error percentages of 1.27%, 0.033%, 0.133%, and 0.1165%, respectively. All values remained within the acceptable error tolerance of ±10%, indicating that the speed control system operates accurately and consistently. Timer functionality was tested at preset durations of 3 minutes (180 seconds), 6 minutes (360 seconds), and 9 minutes (540 seconds), each repeated three times. The test results showed a time deviation of 0.34 seconds at 3 minutes, no deviation at 6 minutes, and a deviation of 2.67 seconds at 9 minutes. These results indicate that the timer also performs with a high level of precision. Overall, the tested overhead stirrer has met the standards for measurement accuracy in both speed and time. This demonstrates that the device is suitable for laboratory or research applications that require controlled mixing of liquids with precise timing and speed regulation measurement area.